2011
DOI: 10.1136/jnnp.2010.224873
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic seizures and frontal disconnection: EEG synchronisation study

Abstract: Objective Psychogenic non-epileptic seizures (PNES) are paroxysmal events that, in contrast to epileptic seizures, are related to psychological causes without the presence of epileptiform EEG changes. Recent models suggest a multifactorial basis for PNES. A potentially paramount, but currently poorly understood factor is the interplay between psychiatric features and a specific vulnerability of the brain leading to a clinical picture that resembles epilepsy. Hypothesising that functional cerebral network abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 46 publications
(36 reference statements)
6
59
3
3
Order By: Relevance
“…Contrary to the pattern of decreased synchronization that has been described to occur in pathological dissociation 13 or during hypnosis 17 , in the present study, the analyses of clusters of electrodes revealed no between-group differences in frontal interhemispheric, left frontal-posterior or right frontal-posterior coherences whether in theta or in beta frequency range. In fact, in mediums' group, a nonsignificant increase in average frontal interhemispheric and left frontal-posterior coherence was noted, both in theta and in beta frequency range.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Contrary to the pattern of decreased synchronization that has been described to occur in pathological dissociation 13 or during hypnosis 17 , in the present study, the analyses of clusters of electrodes revealed no between-group differences in frontal interhemispheric, left frontal-posterior or right frontal-posterior coherences whether in theta or in beta frequency range. In fact, in mediums' group, a nonsignificant increase in average frontal interhemispheric and left frontal-posterior coherence was noted, both in theta and in beta frequency range.…”
Section: Discussioncontrasting
confidence: 47%
“…Replicating the few available prior EEG studies on this research field 18,19 , we observed that mediums had greater theta and beta power during the anomalous sensorial experience compared to non-medium controls. The lack of reduction in frontal interhemispheric and frontal-posterior coherence in mediums group during the alleged mediumistic communication clearly differs from the coherence pattern reported in pathological dissociation 13 and during the hypnotic state 17 . The EEG spectral power and connectivity data observed in this sample of experienced and mentally healthy mediums suggest that cognitive control processes seem to be engaged during the anomalous sensorial experiences.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Abnormalities in connectivity and neural networks in PNES have been investigated using EEG and resting state fMRI. Knyazeva et al 100 studied PNES (N=13) and healthy volunteers (N=13) using multivariate phase synchronization in interictal highdensity EEG and did not show any group differences; however, their results show decreased prefrontal and parietal synchronization with a greater number of PNES events. Barzegaran et al 101 further analyzed these results using graph theory, showing that patients with PNES had similar local and global connectivity and small-world structure, and the deficits in local connectivity correlated with the number of PNES per month.…”
Section: Pnesmentioning
confidence: 97%
“…Reduced connectivity has also been shown to distinguish PNES patients from those with epilepsy with a high level of accuracy [37]. Although a study analysing whole-head surface topography of multivariate phase synchronisation in interictal high-density EEG failed to demonstrate any significant differences between 13 patients with PNES and the same number of age-and gender-matched controls, a significant correlation was found between decreased prefrontal and parietal synchronisation and PNES frequency in the patient group [38].…”
Section: Pnes and Healthy Controls Found Patients With Pnes To Have Rmentioning
confidence: 99%